PEMBERLAKUAN CLINICAL PATHWAY DALAM PEMBERIAN LAYANAN KESEHATAN DAN AKIBAT HUKUMNYA: CLINICAL PATHWAY DALAM PEMBERIAN LAYANAN KESEHATAN - Yohanes Firmansyah; Gunawan Widjaja (Yayasan Pendidikan Medika Indonesia, 2022)
A clinical pathway describes the best way to care for a specific diagnosis or procedure, including the sequencing and timing of interventions by doctors, nurses, and other healthcare professionals. It is a relatively new clinical process improvement tool that is gaining traction in hospitals across the United States, Australia, and the United Kingdom. Clinical pathways are created through the collaborative efforts of clinicians, nurses, pharmacists, physiotherapists, and other allied healthcare professionals with the goal of improving patient care quality. Clinical pathways have been shown to reduce unnecessary variation in patient care, reduce discharge delays through more efficient discharge planning, and improve clinical service cost-effectiveness. Clinical pathways' approach and objectives are consistent with those of total quality management (TQM) and continuous quality improvement (CQI), and are essentially the application of these principles to the patient's bedside. This article investigates the increasing use of clinical pathways, their benefits to healthcare organizations, their use as a tool for CQI activities directly related to patient care, and the medico-legal implications involved.